2007
DOI: 10.1158/0008-5472.can-07-2099
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid (GABA) Stimulates Pancreatic Cancer Growth through Overexpressing GABAA Receptor π Subunit

Abstract: Abstract;-Aminobutyric acid (GABA) functions primarily as an inhibitory neurotransmitter in the mature central nervous system, and GABA/GABA receptors are also present in nonneural tissues, including cancer, but their precise function in nonneuronal or cancerous cells has thus far been poorly defined. Through the genome-wide cDNA microarray analysis of pancreatic ductal adenocarcinoma (PDAC) cells as well as subsequent reverse transcription-PCR and Northern blot analyses, we identified the overexpression of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 22 publications
5
134
3
Order By: Relevance
“…In contrast, ERK1/2 is an established regulator of both cellular motility (33,39,40) and cytokeratin expression (34,41). GABA induces ERK1/2 activation in pancreatic (10) and renal cancers (21), hence we postulated that GABRP stimulates BLBC motility through ERK1/2 regulation of basal-like cytokeratin expression. Indeed, treatment with an ERK1/2 inhibitor recapitulated the decrease in migration and cytokeratin expression observed with diminished GABRP.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, ERK1/2 is an established regulator of both cellular motility (33,39,40) and cytokeratin expression (34,41). GABA induces ERK1/2 activation in pancreatic (10) and renal cancers (21), hence we postulated that GABRP stimulates BLBC motility through ERK1/2 regulation of basal-like cytokeratin expression. Indeed, treatment with an ERK1/2 inhibitor recapitulated the decrease in migration and cytokeratin expression observed with diminished GABRP.…”
Section: Discussionmentioning
confidence: 95%
“…GABA(A) agonists can also induce ERK1/2 phosphorylation in cancer cell lines (10,21). Like calcium signaling, ERK1/2 signaling is pro-migratory (33,39,40), and importantly, regulates cytokeratin expression in non-breast cancer cell lines (34,41).…”
Section: Gabrp Correlates With the Blbc Subtype And Decreasedmentioning
confidence: 99%
“…Taken together, these data indicate that glycolic acid does not serve as a precursor for Neu5Gc in CMAH-deficient human and mouse cells and that CMAH is likely the only endogenous source of Neu5Gc production in mammalian cells. However, increased levels of ␥-aminobutyric acid (GABA) have been found in various tumors (65)(66)(67)(68), an additional precursor of glycolyl-CoA. This led to the hypothesis that Neu5Gc might only be re-expressed under certain metabolic conditions found in tumors.…”
Section: Exogenous Glycolate Does Not Contribute To the N-glycolyl Grmentioning
confidence: 99%
“…Previous studies have shown that GABA stimulates the growth of a variety of types of cancer (23,24). The key enzyme for GABA synthesis is GAD which appears in two isoforms, GAD65 and GAD67, named according to their molecular weights (25).…”
Section: % CI For Exp(b) --------------------------------------mentioning
confidence: 99%